INTEGRASI ILMU PENGETAHUAN, TEKNOLOGI, DAN SENI (IPTEKS) DENGAN NILAI-NILAI AL-QUR’AN - Ahmad Fahmi Romli; Nasrul Syarif; Mavatih Fauzul ‘Adziima (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to examine the nature of Science, Technology, and Arts (IPTEKS) from an Islamic perspective, including its definition, the interrelationship among its components, as well as its roles and contributions to human life. In Islamic thought, IPTEKS is not merely understood as an instrument for worldly advancement but also as a means of drawing closer to Allah SWT. This research emphasizes the importance of integrating spiritual values with the development of science and technology so that progress does not contradict the moral, ethical, and environmental sustainability principles taught in Islam. The method used in this research is library research, analyzing various relevant national and international literature sources, including books, scientific articles, journals, and digital references. The findings indicate that Islam strongly encourages its followers to seek knowledge, advance technology, and produce artistic works, as long as these efforts bring benefit, do not harm the environment, and remain within the framework of Islamic teachings.